Heme catabolism by heme oxygenase-1 confers host resistance to Mycobacterium infection - Silva-Gomes, Sandro (2015)
Heme oxygenases (HO) catalyze the rate-limiting step of heme degradation. The cytoprotective action of the inducible HO-1 isoform, encoded by the Hmox1 gene, is required for host protection against systemic infections. Here we report that upregulation of HO-1 expression in macrophages (M) is strictly required for protection against mycobacterial infection in mice. HO-1-deficient (Hmox1(-/-)) mice are more susceptible to intravenous Mycobacterium avium infection, failing to mount a protective granulomatous response and developing higher pathogen loads, than infected wild-type (Hmox1(+/+)) controls. Furthermore, Hmox1(-/-) mice also develop higher pathogen loads and ultimately succumb when challenged with a low-dose aerosol infection with Mycobacterium tuberculosis. The protective effect of HO-1 acts independently of adaptive immunity, as revealed in M. avium-infected Hmox1(-/-) versus Hmox1(+/+) SCID mice lacking mature B and T cells. In the absence of HO-1, heme accumulation acts as a cytotoxic pro-oxidant in infected M, an effect mimicked by exogenous heme administration to M. avium-infected wild-type M in vitro or to mice in vivo. In conclusion, HO-1 prevents the cytotoxic effect of heme in M, contributing critically to host resistance to Mycobacterium infection.